The Challenges of a Changing Communication Landscape: An Examination of Saudi Arabian Media - Shawli, Nidaa Khalid (Université d'Ottawa / University of Ottawa, 2021)
The purpose of this thesis research was to gain a better understanding of the forces shaping the Saudi newspapers and to identify possible strategies to preserve their readership and generate revenue from the online stream. The research focused on two aspects of the newspaper business—the reader and the newspaper side. This research used analytical research to compare similarities and differences between strategies implemented by Western with those in Saudi newspaper organizations. The research also used an exploratory mixed-method approach to gain in-depth knowledge about the current situation in the Saudi Arabian newspaper industry. The second approach expanded to include two stages: qualitative research focused on Okaz newspaper as a case study and quantitative research carried out through a questionnaire survey. The data collection methods consisted of 11 in-depth, one-on-one interviews with employees of the Okaz daily newspaper, along with statistical data and reports gathered from the organization. Quantitative research was carried out through a questionnaire surveying 212 newsreaders. The findings revealed many similarities between Western and Saudi newspapers regarding the adopted business strategies and some differences in the considered practices to overcome the financial challenges in the business. Moreover, the use of the Latent Class Model revealed four clusters of readers in which only three showed future intention to pay for online news. This research contributes unique knowledge and adds to the overall literature about the state of the newspaper business in Saudi Arabia. It also shed light on Okaz as a case of a local Saudi newspaper facing such challenges. This research also adds value by understanding Saudi newsreaders’ characteristics, reading consumption patterns, different motivations, and their intentions toward paying for news online.
Keywords: Saudi Arabia; Newspaper business; The West; Marketing strategies; 2008/2009 Crisis; Latent Class Model; Uses and Gratification; Attention economy; Ansoff’s Matrix